A case of mucoid hypertrophic degeneration of anterior cruciate ligament with ganglion cyst causing extension block treated with arthroscopic debridement of the cyst and partial debulking surgery - Jain, Vicky T.; Katti, Shubham N.; Yadav, Vijay P.; Paigude, Prithviraj A. (International Journal of Research in Orthopaedics, 2022)
Mucoid degeneration of anterior cruciate ligament (ACL) is an uncommon cause of knee pain and restriction of movements. It uncommonly presents with a coexisting ACL ganglion cyst. Typically present between ages of 40-60 years, however, the true incidence and symptoms are variable. We present our experience with one such case with loss of knee extension treated with arthroscopic debulking. The patient regained both full range of motion and resolution of symptoms after the treatment.